PENGARUH ECONOMIC VALUE ADDED (EVA) DAN RASIO PROFITABILITAS TERHADAP HARGA SAHAM - Venni Agnatia; Diah Amalia (Pusat P2M Politeknik Negeri Batam, 2018)
The purpose of this research is to analyze the effect of Economic Value Added (EVA) and profitability ratios partially and simultaneously to the coal mining company’s stock price. The profitability ratios used in this research as independent variable are Return on Asset (ROA), Return on Equity (ROE), Return on Investment (ROI) and Net Profit Margin (NPM) although the stock price as the dependent variable. The samples used were 14 companies from 25 coal mining companies listed in Indonesia Stock Exchange during the period 2011-2017 so total data processed is 98 samples. This research used linear regression analysis with Eviews version 9. The result indicated that partially the variable ROA and ROI has significant positive effect on stock price. EVA, ROE and NPM does not affect the stock price. All variables simultaneously affect to the stock price. Keyword: EVA, ROA, ROE, ROI, NPM, Stock Price